Kesehatan hidung siswa-siswi Sekolah Menengah Pertama Negeri 4 Pineleng - Pakiding, Pebrianto A.; Pelealu, Olivia C.P.; Mengko, Steward K. (e-CliniC, 2016)
Abstract: Environmental factors play some important roles in human health. Environmental changes influence the nose function. This study was aimed to obtain the nose health status of students at SMPN 4 (Junior High School) Pineleng. This was a descriptive observational study with a cross sectional design. Respondents were students of SMPN 4 Pineleng. There were 25 respondents consisted of 13 males and 12 females. The results of the examination showed normal nose health status in 18 students and abnormalities in 7 students. Examination of the nasal cavity revealed narrow nasal cavity 12%. Examination of the concha revealed pale and hyperthrophy concha 8%; hyperemia 4%; hypertrophy 4% in the left nostril; and pale accompanied with edema and hypertrophy 4% on the right nostril. Examination of the mucosa showed the percentage of livide mucosa 12% in the right nostril and 8% in the left nostril; and hyperemia 4% in the left nostril. Examination of secretion showed serous secretion 12% in the right nostril and 8% in the left nostril. Examination of the septum showed septum deviation 4% in the left nostril meanwhile post nasal drip was found as many as 4%. Conclusion: Most students of SMPN 4 Pineleng had good nasal health status. Keywords: nose health, nose examination Â Abstrak: Lingkungan merupakan faktor terbesar yang memengaruhi kesehatan. Perubahan lingkungan memberikan pengaruh terhadap fungsi hidung. Penelitian ini bertujuan untuk mengetahui kesehatan hidung pada siswa-siswi SMPN 4 Pineleng. Jenis penelitian ialah deskriptif survei dengan desain potong lintang. Responden penelitian ialah siswa-siswi Sekolah Menengah Pertama Negeri 4 Pineleng. Terrdapat 25 responden yang mengikuti penelitian terdiri dari 13 laki-laki dan 12 perempuan. Pemeriksaan hidung mendapatkan hasil normal pada 18 responden dan kelainan pada 7 responden. Pada pemeriksaan kavum nasi kelainan yang ditemukan berupa kavum nasi sempit 12%; konka pucat dan hipertrofi 8%; hiperemis 4%; hipertrofi 4% hidung kiri; edema disertai pucat dan hipertrofi 4% hidung kanan. Pemeriksaan mukosa livide 12% hidung kanan, dan 8% hidung kiri; hiperemis 4% hidung kiri. Pada pemeriksaan sekret, serous 12% hidung kanan dan 8% hidung kiri. Pada pemeriksaan septum, deviasi 4% hidung kiri. Persentase post nasal drip 4%. Simpulan: Sebagian besar siswa-siswi SMPN 4 Pineleng mempunyai kesehatan hidung yang baik. Kata kunci: kesehatan hidung, pemeriksaan hidung